Arduino wearables - Olsson, Tony, ....- ([Berkeley, Calif.] : Apress : Distributed to the book trade worldwide by Springer Science+Business Media, 2012)
This book is an introduction to wearable computing, prototyping, and smart materials using the Arduino platform. Every chapter takes you all the way from idea to finished project. Even if you have no experience with Arduino, this book will get you set up with all the materials, software, and hardware you need; you'll complete simple projects first, and then build on your growing expertise to make more complex projects
Includes bibliographical references (p. 13) and index.
Keywords: Arduino (Programmable controller).; Wearable computers; Smart materials